Correlation Between ED Symptoms and Clinical Outcomes in the Patient with Aneurysmal Subarachnoid Hemorrhage - Adkins, Kristin (2011)
INTRODUCTION: Aneurysmal subarachnoid hemorrhage (aSAH) is a devastating neurologic insult often presenting to the emergency department as a headache. Recognition and prompt treatment are important to good outcomes. The purpose of this analysis was to examine the presentation of aSAH patients to the emergency department and determine whether presentation predicts length of stay or death. METHODS: This is a retrospective review of data gathered from 2 existing studies. Data from patients diagnosed with acute aSAH were reviewed for symptoms, clinical presentation, history, demographics, and laboratory results. Statistical analysis was completed by use of χ(2) and regression analysis. RESULTS: This sample of 193 adult aSAH patients confirmed headache as well as meningeal signs as the most frequent symptom on presentation to the emergency department, and this was cited as the most common reason for seeking medical treatment. Symptom presentation did not appear to affect length of stay; however, survival analysis showed that patients who presented with a Hunt and Hess grade greater than 3 along with bradycardia were 15.6 times more likely to die within the first month of aSAH. DISCUSSION: Although aSAH presentation remains the same, this analysis did find a correlation between poor clinical grade and bradycardia to be a significant predictor of death at 30 days. Additional study may help to determine whether any intervention could lessen this effect. Although patient diagnosis and referral from the community emergency department to a tertiary center were relatively quick, there was a wide window of time between patient recognition of symptoms and seeking medical treatment.